2021
DOI: 10.1139/bcb-2020-0121
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of bovine buttermilk, whey, and lactoferrin on the innate immunity receptors and oxidative status of intestinal epithelial cells

Abstract: Milk contains active molecules with important functional properties as the defensive proteins; among them are the whey protein lactoferrin and proteins of the milk fat globule membrane (MFGM) present in buttermilk. The aim of this study has been to investigate the effect of lactoferrin, whey and buttermilk as modulators of intestinal innate immunity and oxidative stress on intestinal epithelial cells, to evaluate its potential use for the development of functional foods. Innate immune Toll-like receptors (TLR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
2
8
0
1
Order By: Relevance
“…4A). These results agree with those obtained in the study by Buey et al (2021), in which LF showed a positive effect in reducing oxidative stress caused to the cells by LPS. However, in our study, the protective effect of LF against C. sakazakii was greater at lower concentration (0.5 mg mL À1 ), while in the study by Buey et al (2021), the concentration of 10 mg mL À1 was the one with greater effect reversing oxidation caused by LPS.…”
Section: Effect Of Lactoferrin On Inhibition Of C Sakazakii Internali...supporting
confidence: 93%
See 1 more Smart Citation
“…4A). These results agree with those obtained in the study by Buey et al (2021), in which LF showed a positive effect in reducing oxidative stress caused to the cells by LPS. However, in our study, the protective effect of LF against C. sakazakii was greater at lower concentration (0.5 mg mL À1 ), while in the study by Buey et al (2021), the concentration of 10 mg mL À1 was the one with greater effect reversing oxidation caused by LPS.…”
Section: Effect Of Lactoferrin On Inhibition Of C Sakazakii Internali...supporting
confidence: 93%
“…In our previous study of Buey et al (2021) the effect of LF, incubated for 24 h, was evaluated on the basal oxidative stress of Caco-2/TC7 cells. When the cells were incubated with LF, it did not seem to modify by itself the lipid or protein oxidative status of Caco-2/TC7 cells.…”
Section: Effect Of Lactoferrin On Inhibition Of C Sakazakii Internali...mentioning
confidence: 99%
“…Previous study showed that MFGM supplementation improved the intestinal permeability, and therefore reduced the gut derived endotoxin translocated to the liver (18). Furthermore, lactoferrin and whey proteins, as the bioactive components of MFGM, have been shown to reduce oxidative stress (28). As such, the supplementation with MFGM might contribute to the overall downregulation effects on autophagy in SBS through decreasing the levels of liver endotoxin and oxidative stress.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of bLF as a regulator of intestinal innate immunity and oxidative stress on IECs was investigated in a previous study. Innate immune Toll-like receptors (TLRs) mRNA expression, lipid peroxidation, and protein carbonyl levels were determined in enterocyte-like Caco-2/TC7 cells incubated with bLF for 24 h. Results demonstrated that bLF seemed to maintain redox homeostasis and modulate inflammatory response via activation of TLRs when exposed to LPS ( 89 ). Additionally, LF reduced intracellular ROS level and malondialdehyde (MDA) level as well as upregulated glutathione peroxidase (GSH-Px) activity and the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) protein ( 36 ).…”
Section: Immunomodulatory Role Of Lactoferrin In Intestine Mucosal Immune Systemmentioning
confidence: 99%